Translators Across Languages: Meta-Linguistic , Psychological, Social and Hermeneutic Study with Reference to Audio-Visual Translation (Journal of the College of Languages (JCL), 2023)
The widely-held ideology that language is the reflection of its speakers is the hypothesis upon which this study is based. To verify this hypothesis, a fifty-one second clipped video broadcasted by Euronews agency, along with the realization of this footage in four languages (English, French, Arabic and Persian) are subjected to linguistic –metalinguistic analysis. The footage is differently envisaged, thus putting 'the journalistic code of ethics' and the notion of neutrality under scrutiny. The investigation first showed varying lengths in the realization of the footage across the four languages under investigation, with English being, by far, the most condensed language and Arabic being the least, with French and Persian intermediating between them. Other differences point to political-ideological differences where English manifests itself to be highly indicative due to its early tradition in the field of politics. French has, on the other hand, highlighted key values pertinent to the French society such as focus on democracy while Arabic dictates clearly the Arab's predictive-assertive build up of their mentality of the Arabs through the heavy use of future "س – will". Finally, Persian language has hermeneutically reflected the Persian mentality of being focusable on minute details and extra-explanations of surrounding details.